DEVELOPMENTS IN ENTREPRENEURIAL COMPETENCE LITERATURE: TOWARDS THE FUTURE OF WORK - Marcella Riwo Abudho (PEOPLE: International Journal of Social Sciences, 2026)
The innovative human capital in global economic development cannot go unnoticed in such times of change with a focus on sustainability. Research has long shown that the intermateriality across social, economic, and political facets is a manifestation of the change created by entrepreneurship. Entrepreneurship is therefore not just a venture creation process but a driver of civilization. Entrepreneurial learning has been evolving since the proposal of the first entrepreneurship course, dubbed ‘Management of New Enterprises,’ at Harvard Business School in 1947. The diversity of educational aims, methods in teaching, and approaches in monitoring and evaluation has led to the heterogeneity in the definition of concepts around entrepreneurship, including entrepreneurship competence, entrepreneurial education, and entrepreneurship practice. Entrepreneurs have been described by a variety of terms, and various studies have concluded that there is no scientific definition that has been agreed upon for the concept. The ever-growing engagements in entrepreneurial competence in research and practice has led to a diversity of perspectives and models that all make a contribution to the field. While referring to early entrepreneurial literature, studies have concluded that individual intentions and subsequent behaviors bring the emergence of new business organizations, and as this process evolves over time, entrepreneurial intentions are witnessed across business formations.